2018
DOI: 10.1111/gwmr.12254
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Analytical Model to Predict Subsurface LNAPL Distributions and Transmissivity from Current and Historic Fluid Levels in Groundwater Wells: Comparing Results to Numerical Simulations

Abstract: This column reviews the general features of PHT3D Version 2, a reactive multicomponent transport model that couples the geochemical modeling software PHREEQC-2 (Parkhurst and Appelo 1999) with three-dimensional groundwater flow and transport simulators MODFLOW-2000 and MT3DMS (Zheng and Wang 1999). The original version of PHT3D was developed by Henning Prommer and Version 2 by Henning Prommer and Vincent Post (Prommer and Post 2010). More detailed information about PHT3D is available at the website http://www.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…These authors have demonstrated that a high LNAPL saturation can sustain high concentrations over a time scale that could span decades, while a low saturation would completely deplete the LNAPL within a few years. The difficulty in obtaining reliable values of may hamper the accurate prediction of LNAPL depletion using our approach; however, reliable estimates of this parameter may be derived from the floating phase thickness in monitoring wells, as demonstrated by Jeong and Chaberneau [8] and Lenhard et al [12]. Alternatively, Gatsios et al [16] and Teramoto et al [49] demonstrated that may be estimated by the laser-induced fluorescence method via empirical models.…”
Section: Depletion With a Change In The Lnapl Saturationmentioning
confidence: 92%
See 2 more Smart Citations
“…These authors have demonstrated that a high LNAPL saturation can sustain high concentrations over a time scale that could span decades, while a low saturation would completely deplete the LNAPL within a few years. The difficulty in obtaining reliable values of may hamper the accurate prediction of LNAPL depletion using our approach; however, reliable estimates of this parameter may be derived from the floating phase thickness in monitoring wells, as demonstrated by Jeong and Chaberneau [8] and Lenhard et al [12]. Alternatively, Gatsios et al [16] and Teramoto et al [49] demonstrated that may be estimated by the laser-induced fluorescence method via empirical models.…”
Section: Depletion With a Change In The Lnapl Saturationmentioning
confidence: 92%
“…The parameter A may be estimated using , as previously demonstrated by Helder and Celia [50], Culligan et al [51], and Brusseau et al [52]; however, for practical purposes, this parameter may be optimized manually by trial-and-error during model calibration. The difficulty in obtaining reliable values of S nw may hamper the accurate prediction of LNAPL depletion using our approach; however, reliable estimates of this parameter may be derived from the floating phase thickness in monitoring wells, as demonstrated by Jeong and Chaberneau [8] and Lenhard et al [12]. Alternatively, Gatsios et al [16] and Teramoto et al [49] demonstrated that S nw may be estimated by the laser-induced fluorescence method via empirical models.…”
Section: Depletion With a Change In The Lnapl Saturationmentioning
confidence: 93%
See 1 more Smart Citation
“…An assumption is made in the model that the predictions are not dependent on whether the historical highest or lowest fluid level elevations in a well occur first. Numerical simulations suggested that this assumption is reasonable [14].…”
Section: Modelmentioning
confidence: 93%
“…The tests indicate that the proposed methodology is a promising alternative to predict the behavior of dissolved plumes over time contemplating the condition of depletion of the source zone. mento (FARR et al, 1990, MARINELLI & DURNFORD, 1996, KEMBLOWSKI & CHIANG, 1990, JEONG & CHARBENEAU, 2014LENHARD et al, 2018). A condição de trapeamento foi demonstrada por incontáveis trabalhos, incluindo Pede (2009), Suthersan et al (2015), Flores et al (2016, Gatsios et al (2018) e Isler et al (2018).…”
Section: Introductionmentioning
confidence: 99%